Cloning and characterization of cDNA encoding glyoxal oxidase, a H2O2-producing enzyme from the lignin-degrading basidiomycete Phanerochaete chrysosporium. - Kersten, P J (1993)
Glyoxal oxidase is produced by ligninolytic cultures of the white-rot fungus Phanerochaete chrysosporium and is a source of the extracellular H2O2 that is required by ligninolytic peroxidases. We report here the cloning and characterization of glx-1c cDNA, which encodes glyoxal oxidase. The deduced mature protein has 537 amino acids, a molecular size of 57 kDa, and a pI of 5.1. Five potential N-glycosylation sites are present. The predicted N-terminal sequence is identical to the experimentally determined sequence of purified enzyme and is preceded by a leader peptide of 22 amino acids. The sequence of glx-1c lacks significant homology with known sequences. Specific comparisons were made between the glx-1c translated sequence and that of galactose oxidase from Dactylium dendroides because of previously observed catalytic similarities of the enzyme. Although no significant homology is observed, in both cases extensive beta-sheet regions are predicted from the primary sequences. Glyoxal oxidase activity correlates with transcript levels and is also coordinate with the lignin peroxidases in nutrient nitrogen-starved cultures.